2002
DOI: 10.1067/mva.2002.120046
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic scoring of vascular occlusive disease in the diabetic foot: Relevance to bypass graft patency and limb salvage

Abstract: In patients with diabetes mellitus, the foot score is a useful tool for predicting the likelihood of graft patency and limb salvage for infrapopliteal revascularization. However, the relatively high bypass success rate (70%) in the presence of a high foot score (>or= 7) does not allow its use in identifying the subgroup of patients who are unlikely to benefit from bypass grafting surgery. It cannot be used as a means of selecting patients for primary amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 5 publications
(11 reference statements)
0
27
0
1
Order By: Relevance
“…Our series adds important data points to previous studies and also confirms findings from those studies. [7][8][9][10][11][12] In 1998, Faglia et al 8 reported that half of their patients with diabetic foot ulcers had stenoses in the popliteal and tibial arteries only; however, no data are provided specific to occlusions present in these vessels. In 2002, van der Feen et al 12 confirmed that lower limb atherosclerosis in DM is more severe in distal arteries, but this study population included patients with and without CLI.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our series adds important data points to previous studies and also confirms findings from those studies. [7][8][9][10][11][12] In 1998, Faglia et al 8 reported that half of their patients with diabetic foot ulcers had stenoses in the popliteal and tibial arteries only; however, no data are provided specific to occlusions present in these vessels. In 2002, van der Feen et al 12 confirmed that lower limb atherosclerosis in DM is more severe in distal arteries, but this study population included patients with and without CLI.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 Previous work on patterns of arterial occlusion in CLI has focused on patients with diabetes mellitus (DM). [7][8][9][10][11][12] Although 60% to 70% of patients with CLI have DM, 13,14 a third do not, which limits the available database that would fully characterize the population. A more comprehensive description of disease location and anatomy would facilitate the planning of clinical trials, such as angiogenesis studies, that could use specific disease distribution information.…”
mentioning
confidence: 97%
“…Traditional study end points for these patients have included graft patency, 1,2 limb salvage, 3,4 or death. 5,6 More recently, however, alternative end points have emerged that include amputation-free survival, 79 major adverse cardiovascular events, 9 target limb revascularization, 10 quality of life, 11 and functional outcomes such as the ability to ambulate or to live independently after surgery.…”
mentioning
confidence: 99%
“…Baseline risk estimation is important for the evaluation of treatment outcome in patients with peripheral arterial disease. 33,34 Definition of the patient populations in studies assessing the efficacy of therapies of peripheral arterial disease is often complex and previously defined criteria and estimation of baseline risk have been disputed. 26,27 Comparison of studies is therefore difficult.…”
Section: Discussionmentioning
confidence: 99%